Positive electrode active material, all-solid-state battery, and method for producing positive electrode active material

By applying a composite oxide coating composed of P, B and O on the surface of the positive electrode active material of a sulfide all-solid state battery, and controlling the content ratio of Li and Na, the problem of increasing internal resistance caused by the degradation of sulfide solid electrolyte is solved, and the effect of improving battery performance and reducing production costs is achieved.

JP7661993B2Active Publication Date: 2025-04-15TOYOTA JIDOSHA KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023051115
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2025-04-15
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

In a sulfide all-solid state battery, when the sulfide solid electrolyte comes into direct contact with the positive electrode active substance, it will lead to deterioration of the electrolyte and increase the internal resistance of the battery.

Method used

A coating film containing phosphorus (P), boron (B) and oxygen (O) is used as the main components, covering the surface of the positive electrode active material, and sodium (Na) and sodium (Li) are added as optional components to the coating film to form a composite oxide coating. The coating film ensures that the Li content ratio is 1.5 or less and the Na content ratio is 1.34 or less by adjusting the content ratio of Li to Na to reduce the internal resistance of the battery.

Benefits of technology

By using a composite oxide coating composed of P, B and O, the internal resistance of the battery is significantly reduced, the performance of the battery is improved, and the use of cheaper and low polymerization raw materials is allowed, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661993000001
    Figure 0007661993000001
  • Figure 0007661993000002
    Figure 0007661993000002
  • Figure 0007661993000003
    Figure 0007661993000003
Patent Text Reader

Abstract

To reduce battery resistance.SOLUTION: A positive electrode active material includes active material particles and a coating film. The coating film covers at least a part of the surface of the active material particles. The coating film includes P, B, and O as essential components, and further includes Li and Na as optional components. The positive electrode active material satisfies the relationship of "Formula (1): CLi / (CP+CB)≤1.50" and "Formula (2): CNa / (CP+CB)≤1.34". CLi, CP, CB, and CNa each represent an element concentration measured by X-ray photoelectron spectroscopy. CLi represents an element concentration of lithium. CP represents an element concentration of phosphorus. CB represents an element concentration of boron. CNa represents an element concentration of sodium.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a positive electrode active material, an all-solid-state battery, and a method for producing a positive electrode active material. [Background technology]

[0002] Japanese Patent Application Laid-Open No. 2003-338321 (Patent Document 1) discloses forming a film of an inorganic solid electrolyte between a positive electrode material and an organic electrolyte. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2003-338321 A Summary of the Invention [Problem to be solved by the invention]

[0004] A sulfide-based all-solid-state battery (hereinafter may be abbreviated as "all-solid-state battery") has been developed. The all-solid-state battery includes a sulfide solid electrolyte. In the positive electrode, the active material particles have a high potential. When the sulfide solid electrolyte comes into direct contact with the active material particles in the positive electrode, the sulfide solid electrolyte may deteriorate. The deterioration of the sulfide solid electrolyte (ion conduction path) may increase the battery resistance. Therefore, it has been proposed to form a coating film on the surface of the active material particles. The coating film prevents direct contact between the active material particles and the sulfide solid electrolyte, so that the deterioration of the sulfide solid electrolyte can be reduced. Conventionally, it has been proposed to form a coating film using an oxide solid electrolyte such as Li3PO4 (see, for example, Patent Document 1).

[0005] An object of the present disclosure is to reduce battery resistance. [Means for solving the problem]

[0006] 1. The positive electrode active material includes active material particles and a coating film. The coating film covers at least a part of the surface of the active material particles. The coating film includes P, B, and O as essential components, and further includes Li and Na as optional components. The positive electrode active material satisfies the relationship of the following formula (1) and the following formula (2). C Li / (C P +C B )≦1.50 …(1) C Na / (C P +C B )≦1.34 …(2) In the above formula (1) and the above formula (2), C Li , C P , C B and C Na indicates the element concentration measured by X-ray photoelectron spectroscopy. Li indicates the elemental concentration of lithium. P indicates the elemental concentration of phosphorus. B indicates the elemental concentration of boron. Na indicates the elemental concentration of sodium.

[0007] Hereinafter, the left side of the above formula (1) "C Li / (C P +C B )" is also referred to as the "Li composition ratio". Na / (C P +C B )" is also written as "Na composition ratio."

[0008] In Li3PO4, the Li composition ratio is 3. It is believed that the Li in Li3PO4 (oxide solid electrolyte) promotes ion conduction (Li conduction). Therefore, the higher the Li composition ratio, the lower the battery resistance is expected to be. However, contrary to expectations, it has been found that a lower Li composition ratio can reduce battery resistance. Furthermore, as shown in the above formula (1), it has been found that a Li composition ratio of 1.5 or less significantly reduces battery resistance.

[0009] As a result of extensive research into various phosphoric acid compounds, it has become clear that it is difficult to reduce battery resistance when a phosphoric acid compound with a low degree of polymerization (orthophosphoric acid) is used as the raw material. Furthermore, it has been found that it is difficult to reduce battery resistance when the raw material contains impurities such as Na. As a result, it becomes necessary to use expensive raw materials (high degree of polymerization, high purity).

[0010] In the positive electrode active material described in "1" above, the coating film contains a complex oxide. That is, the coating film further contains B in addition to P and O. P, B and O can form a glass network. When the glass network contains two types of anions (PO-based anion and BO-based anion), a mixed anion effect is expected to be exhibited. The mixed anion effect can significantly increase ion conductivity.

[0011] Furthermore, although the details of the mechanism are unclear, a coating film containing P, B, and O can have robustness. That is, the coating film may contain a small amount of Na. Even if the coating film contains a small amount of Na, a reduction in battery resistance can be expected. Furthermore, a reduction in battery resistance can also be expected by using phosphoric acid raw materials with a low degree of polymerization. Therefore, the use of inexpensive raw materials (low degree of polymerization, low purity) can also be tolerated.

[0012] However, as shown in the above formula (2), the Na composition ratio is 1.34 or less. If the Na composition ratio exceeds 1.34, even if the Li composition ratio is 1.5 or less and the coating film contains B, the desired battery resistance may not be obtained.

[0013] 2. The positive electrode active material described in the above "1" may include, for example, the following configuration: The coating film includes Na as an essential component. The relationship of the following formula (3) and the following formula (4) are satisfied. C Li / (C P +C B )≦1.27 …(3) 0.24≦C Na / (C P +C B ) …(4)

[0014] 3. The positive electrode active material according to the above "1" or "2" may include, for example, the following configuration. The positive electrode active material has a coverage of 94% or more. The coverage is measured by X-ray photoelectron spectroscopy. With a coverage of 94% or more, a reduction in battery resistance is expected.

[0015] 4. The all-solid-state battery includes a positive electrode and a negative electrode. The positive electrode includes the positive electrode active material according to any one of the above items "1" to "3" and a sulfide solid electrolyte.

[0016] 5. A method for producing a positive electrode active material includes the following (a) and (b): (a) A mixture is prepared by mixing a coating liquid with active material particles. (b) The mixture is dried to produce a positive electrode active material. The coating liquid contains a solute and a solvent. The solute contains a phosphoric acid compound and a boric acid compound as essential components, and contains at least one selected from the group consisting of a lithium compound, a sodium salt, and an ammonium salt as an optional component.

[0017] The coating liquid contains both a phosphoric acid compound and a boric acid compound, so that a coating film containing P, B, and O can be formed. When the coating liquid contains both a phosphoric acid compound and a boric acid compound, a raw material containing a Na salt and an NH4 salt may be used. Even if the coating liquid contains a Na salt and an NH4 salt, a reduction in battery resistance is expected. For example, at least a part of the phosphoric acid compound may be a Na salt. For example, at least a part of the boric acid compound may be an NH4 salt. Note that Na derived from the Na salt may be included in the coating film. N derived from the NH4 salt may be discharged outside the system during the formation of the coating film.

[0018] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the present embodiment do not limit the technical scope of the present disclosure. The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are non-restrictive. The technical scope of the present disclosure encompasses all modifications within the meaning and scope equivalent to the description of the claims. For example, it is originally intended that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a conceptual diagram of the positive electrode active material in this embodiment. [Diagram 2] FIG. 2 is a schematic flow chart of the method for producing the positive electrode active material in this embodiment. [Diagram 3] FIG. 3 is a conceptual diagram of the all-solid-state battery in this embodiment. [Figure 4] FIG. 4 is a table showing the experimental results. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] <Terminology explanation> "Element concentration (C Li , C P , C B , C Na) indicates a value measured in the following procedure. The elemental concentration is measured by X-ray photoelectron spectroscopy (XPS). XPS acquires composition information of the outermost surface of the measurement target. For example, an XPS device manufactured by ULVAC-PHI (product name: PHI X-tool) or an equivalent product may be used. The positive electrode active material (powder) is set in the XPS device. Narrow scan analysis is performed with a pass energy of 224 eV. The measurement data is processed by analysis software. For example, analysis software manufactured by ULVAC-PHI (product name: MulTiPak) or an equivalent product may be used. The peak area (integral value) of the Li1s spectrum is the elemental concentration of Li (C Li ) The peak area of ​​the P2p spectrum is converted to the elemental concentration of P (C P ) The peak area of ​​the B1s spectrum is converted to the elemental concentration of B (C B ) The peak area of ​​the Na1s spectrum is converted to the elemental concentration of Na (C Na )

[0021] The "coverage" refers to a value measured by the following procedure. The XPS data obtained above is analyzed, and the element concentration is determined from the peak areas of C1s, O1s, B1s, P2p, M2p3, etc. The coverage is calculated using the following formula (5). θ=(P+B) / (P+B+M) …(5) In the above formula (5), θ represents the coverage. The coverage is expressed as a percentage (%). P, B, and M represent the elemental concentration of each element. M represents the elemental concentration of the constituent elements of the active material particles (excluding Li and O). M may contain at least one element selected from the group consisting of Ni, Co, Mn, and Al. For example, when the active material particles are "LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, the right side of the above formula (5) can be transformed to "(P+B) / (P+B+Ni+Co+Mn)". For example, when the active material particles are "LiNi 0.8 Co 0.15 Al 0.05O2”, the right hand side of the above formula (5) can be transformed to “(P+B) / (P+B+Ni+Co+Al)”.

[0022] Numerical ranges such as "m to n%" include the upper and lower limits unless otherwise specified. In other words, "m to n%" indicates a numerical range of "m% or more and n% or less." Also, "m% or more and n% or less" includes "more than m% and less than n%."

[0023] <Cathode active material> The positive electrode active material may be composed of one particle. The positive electrode active material may contain two or more particles. That is, the positive electrode active material may be a powder (an aggregate of particles). The positive electrode active material may have a D50 of, for example, 1 to 30 μm, 10 to 20 μm, or 1 to 10 μm. "D50" refers to the particle size at which the cumulative distribution is 50% in the volume-based particle size distribution (cumulative distribution). The particle size distribution can be measured by a laser diffraction method.

[0024] 1 is a conceptual diagram of a positive electrode active material in this embodiment. The positive electrode active material 5 includes composite particles. The composite particles have a core-shell structure. That is, the positive electrode active material 5 includes active material particles 1 and a coating film 2. The positive electrode active material 5 can be referred to as, for example, a "coated active material."

[0025] <Coating film> The coating film 2 is a shell of the positive electrode active material 5. The coating film 2 covers at least a part of the surface of the active material particle 1 (core). The coverage may be, for example, 93% or more. The coverage may be, for example, any of 94% or more, 95% or more, 96% or more, or 97% or more. The coverage may be, for example, any of 100% or less, 97% or less, 96% or less, or 95% or less.

[0026] The thickness of the coating film 2 may be, for example, any of 5 to 100 nm, 5 to 50 nm, 10 to 30 nm, or 20 to 30 nm. The thickness of the coating film 2 can be measured, for example, by observing a cross section of the composite particle. The cross section observation can be performed, for example, by a SEM (Scanning Electron Microscope).

[0027] The coating film 2 contains P, B, and O as essential components. P, B, and O can form oxide glass. The oxide glass can include a glass network structure. The coexistence of P and B is expected to produce a mixed anion effect. The oxide glass may include, for example, a phosphate skeleton and a borate skeleton. For example, if the TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry) spectrum of the positive electrode active material 5 contains phosphate ions (e.g., PO2 - , PO3 - Fragment peaks derived from borate ions (e.g. BO2 - , BO3 - etc.) may be included.

[0028] The coating film 2 contains Li as an optional component. Li may be an essential component. In this embodiment, the relationship of the following formula (1) is satisfied. C Li / (C P +C B )≦1.50 …(1) By satisfying the relationship of the above formula (1), a reduction in battery resistance is expected. The origin of Li in the coating film 2 is considered to be two or more. For example, the coating film 2 may contain Li derived from a lithium compound contained in the coating liquid. For example, the coating film 2 may contain Li that has diffused from the active material particles 1 when the coating film 2 is formed.

[0029] For example, the relationship of the following formula (3) may be satisfied. C Li / (C P +CB )≦1.27 …(3) The Li composition ratio may be, for example, any one of 1.11 or less, 1.01 or less, 1.00 or less, 0.89 or less, 0.82 or less, or 0.5 or less. The Li composition ratio may be, for example, any one of 0.5 or more, 0.82 or more, 0.89 or more, 1.00 or more, 1.01 or more, 1.11 or more, or 1.27 or more.

[0030] As long as the relationship of the above formula (1) is satisfied, the quantitative relationship between P and B is arbitrary. For example, P / C B =99 / 1~1 / 99", "C P / C B =9 / 1~1 / 9" or "C P / C B =7 / 3~3 / 7" may be satisfied. For example, "1 ≤ C P / C B " or "2≦C P / C B " may be satisfied.

[0031] The coating film 2 further contains Na as an optional component. Na may be an essential component. In this embodiment, the relationship of the following formula (2) is satisfied. C Na / (C P +C B )≦1.34 …(2) If the Na composition ratio exceeds 1.34, for example, there is a possibility that inconveniences such as an increase in battery resistance may occur. The Na composition ratio may be, for example, any one of 0.84 or less, 0.61 or less, 0.43 or less, 0.37 or less, 0.27 or less, 0.24 or less, or 0.05 or less.

[0032] For example, the relationship of the following formula (4) may be satisfied. 0.24≦C Na / (C P +C B ) …(4) The Na composition ratio may be, for example, any one of 0.05 or more, 0.27 or more, 0.37 or more, 0.43 or more, 0.61 or more, or 0.84 or more.

[0033] <Active material particles> The active material particle 1 is the core of the positive electrode active material 5. The active material particle 1 may have a D50 of, for example, 1 to 30 μm, 10 to 20 μm, or 1 to 10 μm. The active material particle 1 can reversibly store Li ions. The active material particle 1 can have any crystal structure. The active material particle 1 may include, for example, a layered rock salt type structure or the like.

[0034] The active material particle 1 can have any composition. The active material particle 1 may have, for example, the composition of the following formula (6). Li 1-a Ni x M 1-x O2…(6) In the above formula (6), the relationship of -0.5 ≦ a ≦ 0.5 and 0 < x < 1 is satisfied. M is at least one selected from the group consisting of Co, Mn, and Al. For example, the relationship of 0.5 ≦ x < 1 or 0.6 ≦ x ≦ 0.9 may be satisfied.

[0035] A dopant may be added to the active material particle 1. The dopant may be diffused throughout the particle or locally distributed. For example, the dopant may be unevenly distributed on the particle surface. The dopant may be a substitutional solid solution atom or an interstitial solid solution atom. The addition amount of the dopant (mole fraction with respect to the whole of the active material particle 1) may be, for example, 0.01 to 5%, 0.1 to 3%, or 0.1 to 1%. The dopant may include, for example, at least one selected from the group consisting of B, C, N, halogen, Si, Na, Mg, Al, Mn, Co, Cr, Sc, Ti, V, Cu, Zn, Ga, Ge, Se, Sr, Y, Zr, Nb, Mo, In, Pb, Bi, Sb, Sn, W, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and actinoid.

[0036] <Method for manufacturing positive electrode active material> 2 is a schematic flow chart of the method for producing a positive electrode active material in this embodiment. Hereinafter, the "method for producing a positive electrode active material in this embodiment" may be abbreviated as "this production method". This production method includes "(a) preparation of a mixture" and "(b) drying". This production method may further include, for example, "(c) heat treatment" or the like.

[0037] <(a) Preparation of the mixture> The present manufacturing method includes preparing a mixture by mixing a coating liquid with active material particles 1. Details of the active material particles 1 are as described above. The mixture may be, for example, either a suspension or a wet powder. For example, a suspension may be formed by dispersing active material particles 1 (powder) in a coating liquid. For example, a wet powder may be formed by spraying a coating liquid into a powder. In the present manufacturing method, any mixing device, granulating device, etc. may be used.

[0038] The coating liquid includes a solute and a solvent. The coating liquid may further include, for example, a suspension (undissolved component), a precipitate, etc. The solvent may include any component as long as the solute can be dissolved in the solvent. The solvent may include, for example, water, alcohol, etc. The solvent may include, for example, ion-exchanged water, methanol, ethanol, etc.

[0039] The solute includes the raw material of the coating film 2. The amount of the solute may be, for example, 0.1 to 20 parts by mass with respect to 100 parts by mass of the solvent. The solute includes, as essential components, a phosphoric acid compound and a boric acid compound. The phosphoric acid compound is a P source of the coating film 2. The boric acid compound is a B source of the coating film 2. The solute includes, as an optional component, at least one selected from the group consisting of a lithium compound, a Na salt, and an NH4 salt. For example, the solute may be composed of phosphoric acid and boric acid. For example, the solute may include phosphoric acid and boric acid, and in addition to these, may further include a Na salt of phosphoric acid, a Na salt of boric acid, an NH4 salt of phosphoric acid, an NH4 salt of boric acid, or the like. The Na salt of phosphoric acid, or the like, may function, for example, as an excipient, or the like. In the solute, all or a part of the phosphoric acid compound and the boric acid compound may form a Na salt, an NH4 salt, or the like. By replacing all or a part of the raw material with a Na salt, or the like, it is expected that the raw material cost can be reduced. For example, a mixture of metaphosphoric acid and sodium orthophosphate may be used. For example, in condensed phosphoric acid (metaphosphoric acid, etc.), all or some of the phosphoric acid groups may form a Na salt, etc. The phosphoric acid compound may contain, for example, orthophosphoric acid, etc. By using a phosphoric acid compound with a low degree of polymerization, a reduction in raw material costs is also expected. The solute may contain, for example, at least one selected from the group consisting of orthophosphoric acid, polyphosphoric acid, metaphosphoric acid, sodium orthophosphate, sodium polyphosphate, sodium metaphosphate, sodium hexametaphosphate, disodium phosphate, trisodium phosphate, boric acid, sodium metaborate, and NH4 borate. The Na salt and NH4 salt may be, for example, a hydrate.

[0040] The solute may contain a lithium compound so long as the Li composition ratio can be 1.5 or less in the positive electrode active material 5. The lithium compound may contain, for example, lithium hydroxide, lithium nitrate, lithium carbonate, or the like.

[0041] <(b) Drying> This manufacturing method includes producing a positive electrode active material 5 by drying the mixture. The coating liquid attached to the surface of the active material particles 1 is dried to produce a coating film 2. In this manufacturing method, any drying method can be used. For example, the mixture may be dried by a spray dryer. That is, the suspension is sprayed from a nozzle to form droplets. The droplets include the active material particles 1 and the coating liquid. For example, the droplets can be dried by hot air to form the positive electrode active material 5. By using the spray drying method, for example, an improvement in the coverage rate is expected.

[0042] For example, the positive electrode active material 5 may be produced by a tumbling fluidized bed coating apparatus. In the tumbling fluidized bed coating apparatus, "(a) preparation of the mixture" and "(b) drying" can proceed substantially simultaneously.

[0043] <(c) Heat treatment> The present manufacturing method may include subjecting the positive electrode active material 5 to a heat treatment. The coating film 2 may be fixed by the heat treatment. The heat treatment may also be called "baking". In the present manufacturing method, any heat treatment device may be used. The treatment temperature may be, for example, 150 to 300°C. The treatment time may be, for example, 1 to 10 hours. The heat treatment atmosphere may be, for example, either an air atmosphere or an inert atmosphere.

[0044] <All-solid-state battery> FIG. 3 is a conceptual diagram of an all-solid-state battery in this embodiment. The battery 100 may have any shape. The battery 100 may have, for example, a plate-like shape. The battery 100 includes a power generating element 50. The battery 100 may include an exterior body (not shown). The exterior body may house the power generating element 50. The exterior body may be, for example, a pouch made of an Al laminate film. The power generating element 50 includes a positive electrode 10 and a negative electrode 20. The power generating element 50 may further include a separator layer 30. The separator layer 30 is disposed between the positive electrode 10 and the negative electrode 20. The power generating element 50 may have any shape. The power generating element 50 may have, for example, either a monopolar structure or a bipolar structure.

[0045] The positive electrode 10 may include, for example, a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector may include, for example, an Al foil or the like. The positive electrode active material layer is disposed on the surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material and a sulfide solid electrolyte. Details of the positive electrode active material are as described above.

[0046] The amount of the sulfide solid electrolyte may be, for example, 1 to 200 parts by volume relative to 100 parts by volume of the positive electrode active material. The sulfide solid electrolyte may be, for example, glass ceramics or argyrodite. The sulfide solid electrolyte may be, for example, LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-GeS2-P2S5, Li2S-P2S5, Li 10 GeP2S 12 , Li4P2S6, Li7P3S 11 , Li3PS4, Li7PS6, and Li6PS5X (X=Cl, Br, I).

[0047] For example, "LiI-LiBr-Li3PS4" indicates a sulfide solid electrolyte produced by mixing LiI, LiBr, and Li3PS4 in any molar ratio. For example, the sulfide solid electrolyte may be produced by a mechanochemical method. The mixing ratio may be specified by adding a number before each raw material. For example, "10LiI-15LiBr-75Li3PS4" indicates that the raw material mixing ratio is "LiI / LiBr / Li3PS4=10 / 15 / 75 (molar ratio)".

[0048] The positive electrode active material layer may further include, for example, a conductive material and a binder. The blending amount of the conductive material and the binder may be, independently, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the positive electrode active material. The conductive material may include, for example, acetylene black, vapor grown carbon fiber (VGCF), etc. The binder may include, for example, polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), etc. EXAMPLES

[0049] <Sample> The experimental results are shown in a table in Fig. 4. Positive electrode active materials and all-solid-state batteries according to Nos. 1 to 14 were manufactured as follows.

[0050] No.1 A coating liquid was prepared by dissolving 10.8 parts by mass of orthophosphoric acid (content 85%, manufactured by Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water.

[0051] 50 parts by mass of active material particles (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A suspension was prepared by dispersing 53.7 parts by mass of ZnO in the coating liquid. The suspension was supplied to a spray dryer (product name "Mini Spray Dryer B-290", manufactured by BUCHI) to produce the positive electrode active material. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3The positive electrode active material was heat-treated in air at a temperature of 200°C.

[0052] A positive electrode slurry was prepared by mixing the positive electrode active material, sulfide solid electrolyte (10LiI-15LiBr-75Li3PS4), conductive material (VGCF), binder (SBR) and dispersion medium (heptane). The mixture ratio of the positive electrode active material and the sulfide solid electrolyte was "positive electrode active material / sulfide solid electrolyte = 6 / 4 (volume ratio)". The amounts of the conductive material and binder were 3 parts by mass per 100 parts by mass of the positive electrode active material. The positive electrode slurry was thoroughly stirred by an ultrasonic homogenizer. A coating film was formed by applying the positive electrode slurry to the surface of a positive electrode current collector (Al foil). The coating film was dried at 100 °C for 30 minutes by a hot plate. In this way, a positive electrode blank was manufactured. A disk-shaped positive electrode was cut out from the positive electrode blank. The area of ​​the positive electrode was 1 cm2. 2 It was.

[0053] A negative electrode and a separator layer were prepared. The negative electrode active material was graphite. The same type of sulfide solid electrolyte was used between the positive electrode, the separator layer, and the negative electrode. A stack was formed by stacking the positive electrode, the separator layer, and the negative electrode in this order in a cylindrical jig. A power generating element was formed by pressing the stack. A terminal was connected to the power generating element to form an all-solid-state battery.

[0054] No.2 A positive electrode active material and an all-solid-state battery were manufactured in the same manner as in No. 1, except that polyphosphoric acid (product name "Polyphosphoric acid-116T", manufactured by Nippon Chemical Industry Co., Ltd.) was used instead of orthophosphoric acid.

[0055] No.3, No.4 A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (containing sodium) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Except for this, the positive electrode active materials and all-solid-state batteries according to No. 3 and No. 4 were manufactured in the same manner as No. 1. Note that "metaphosphoric acid (containing sodium)" refers to a mixture of metaphosphoric acid and sodium metaphosphate (excipient). The molar ratio "Na / P" in the metaphosphoric acid (containing sodium) was 0.5. The molar ratio "Na / P" refers to the ratio of the amount of Na to the amount of P.

[0056] No.5 A solution was formed by dissolving 10.8 parts by mass of orthophosphoric acid (85% content, Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. A coating solution was prepared by further dissolving boric acid (Nacalai Tesque, Inc.) in the solution so that the molar ratio "P / B" was 1.0. Aside from this, a positive electrode active material and an all-solid-state battery were manufactured in the same manner as in No. 1. The molar ratio "P / B" indicates the ratio of the amount of substance P to the amount of substance B.

[0057] No.6 A positive electrode active material and an all-solid-state battery were manufactured in the same manner as in No. 5, except that polyphosphoric acid (product name "Polyphosphoric acid-116T", manufactured by Nippon Chemical Industry Co., Ltd.) was used instead of orthophosphoric acid.

[0058] No.7 A positive electrode active material and an all-solid-state battery were produced in the same manner as in No. 5, except that metaphosphoric acid (containing sodium) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used instead of orthophosphoric acid.

[0059] No.8 A positive electrode active material and an all-solid-state battery were manufactured in the same manner as in No. 5, except that sodium hexametaphosphate (manufactured by Yoneyama Chemical Industry Co., Ltd.) was used instead of orthophosphoric acid.

[0060] No.9 A positive electrode active material and an all-solid-state battery were produced in the same manner as in No. 5, except that sodium metaphosphate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used instead of orthophosphoric acid.

[0061] No.10 A positive electrode active material and an all-solid-state battery were manufactured in the same manner as in No. 5, except that sodium metaborate (manufactured by Yoneyama Chemical Industry Co., Ltd.) was used instead of boric acid.

[0062] No.11 A positive electrode active material and an all-solid-state battery were produced in the same manner as in No. 5, except that ammonium borate (manufactured by Yoneyama Chemical Industry Co., Ltd.) was used instead of boric acid.

[0063] No.12 A positive electrode active material and an all-solid-state battery were fabricated in the same manner as in No. 5, except that disodium hydrogen phosphate dodecahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used instead of orthophosphoric acid. The molar ratio "Na / P" in disodium hydrogen phosphate dodecahydrate was 2.0.

[0064] No.13 A positive electrode active material and an all-solid-state battery were manufactured in the same manner as in No. 5, except that sodium polyphosphate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used instead of orthophosphoric acid. The molar ratio "Na / P" in sodium polyphosphate was 1.0.

[0065] No.14 A positive electrode active material and an all-solid-state battery were fabricated in the same manner as in No. 5, except that trisodium phosphate dodecahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used instead of orthophosphoric acid. The molar ratio "Na / P" in trisodium phosphate dodecahydrate was 3.0.

[0066] <Evaluation> The Li composition ratio, Na composition ratio, and coverage ratio of each positive electrode active material were measured using an XPS device. The resistance was measured for each all-solid-state battery. The measurement results are shown in FIG.

[0067] <Result> Li composition ratio “C Li / (C P +C B In the range where the Na composition ratio "C )" is 1.5 or less, the battery resistance tends to decrease significantly. Na / (C P +C B ) is in the range of 1.34 or less, the battery resistance tends to stabilize at a low value (No. 5 to No. 13).

[0068] When the coating film does not contain B, even if the Li composition ratio is 1.5 or less and the Na composition ratio is 1.34 or less, the battery resistance tends to be high (No. 4).

[0069] Even if the coating film contains B and the Li composition ratio is 1.5 or less, when the Na composition ratio exceeds 1.34, the battery resistance tends to be high (No. 14). [Explanation of symbols]

[0070] 1 active material particle, 2 coating film, 5 positive electrode active material, 10 positive electrode, 20 negative electrode, 30 separator layer, 50 power generating element, 100 battery.

Claims

1. A positive electrode active material for a positive electrode comprising a sulfide solid electrolyte, The active material particles and the coating film are included. the coating film covers at least a part of the surface of the active material particle, The coating film contains P, B, O, and Na as essential components, and further contains Li as an optional component, Formula (1) and Formula (2): C Li / (C P +C B )≦1.50 …(1) 0.24≦C Na / (C P +C B )≦1.34 …(2) Fulfilling the relationship, In the formula (1) and the formula (2), C Li , C P , C B and C Na indicate element concentrations measured by X-ray photoelectron spectroscopy, C Li indicates the elemental concentration of lithium, and C P indicates the elemental concentration of phosphorus, and C B indicates the elemental concentration of boron, and C Na indicates the elemental concentration of sodium, Cathode active material.

2. Formula (3): C Li / (C P +C B )≦1.27 …(3) Satisfy the relationship The positive electrode active material according to claim 1 .

3. A coverage rate of 94% or more; The coverage is measured by X-ray photoelectron spectroscopy. The positive electrode active material according to claim 1 or 2.

4. A positive electrode and a negative electrode are included, The positive electrode comprises the positive electrode active material according to claim 1 or 2 and a sulfide solid electrolyte. All-solid-state battery.

5. A method for producing the positive electrode active material according to claim 1, comprising: (a) preparing a mixture by mixing a coating liquid with active material particles; and, (b) drying the mixture to produce a positive electrode active material; Including, The coating liquid includes a solute and a solvent, The solute contains, as essential components, a phosphoric acid compound and a boric acid compound, and, as an optional component, at least one selected from the group consisting of a lithium compound, a sodium salt, and an ammonium salt. A method for producing a positive electrode active material.

Citation Information

Patent Citations

  • Secondary battery

    JP2003338321A

  • Glass electrolyte

    JP2015063447A

  • Positive electrode composite material and sulfide all-solid battery arranged by use thereof

    JP2016039062A

  • Electrode for electrochemical devices and nonaqueous electrolyte secondary battery

    WO2022131065A1